ESTRÉS EN EL ADOLESCENTE Y EL COMPORTAMIENTO ESCOLAR EN LOS ESTUDIANTES DE LA UNIDAD EDUCATIVA GLADYS CEDEÑO DE OLIVO - Granja Guagchinga, Wilson Manuel (2023)
The purpose of this research was to formulate the incidence of stress on the school behavior of the students of the Gladys Cedeño de Olivo Educational Unit who would have presented certain symptoms due to traumatic events, absence of loved ones that may lead to certain behaviors that affect performance school and social skills of students both inside and outside the classroom, and even in their own homes. The disposition of the study was specific, using the research linked to the representative level, because by means of the recapitulations and observations it was tried to know the causes and consequences between the two proposed alternatives, in order to clarify the stress in the students, according to unquestionable criteria. It also had an explanatory level because the variables investigated are manifested through the theory and bibliographic research. The proposal presented was established in the bibliographic documentary research to explain in a theoretical and scientific way the proposed research process and the possible alternative solution that generated it. The sample that was worked corresponds to adolescent students of the last years of basic education of the Gladys Cedeño de Olivo Educational Unit, according to the data provided by the Institution and considering a population of 100 students, 100 parents and 10 Teachers